Gray ghost : the life of Col. John Singleton Mosby - Ramage, James A. (University Press of Kentucky, 1999)
Confederate John Singleton Mosby forged his reputation on the most exhilarating of military activities: the overnight raid. Mosby possessed a genius for guerrilla and psychological warfare, taking control of the dark to make himself the "Gray Ghost" of Union nightmares. Gray Ghost, the first full biography of Confederate raider John Mosby, reveals new information on every aspect of Mosby's life, providing the first analysis of his impact on the Civil War from the Union viewpoint.